Associations between Tissue Visfatin/Nicotinamide, Phosphoribosyltransferase (Nampt), Retinol Binding Protein-4, and Vaspin Concentrations and Insulin Resistance in Morbidly Obese Subjects - Goktas, Zeynep; Owens, Shannon; Boylan, Mallory; Syn, David; Shen, Chwan-Li; Reed, Debra B.; San Francisco, Susan; Wang, Shu (Mediators of Inflammation, 2013)
Visfatin/Nampt, vaspin, and retinol binding protein-4 (RBP-4) play an important role in insulin resistance. The objectives of this study were to measure visfatin/Nampt, vaspin, and RBP-4 concentrations in blood, liver, muscle, subcutaneous, omental, and mesenteric adipose tissues in morbidly obese subjects and investigate their relationship to insulin resistance. Blood and tissue samples were collected from 38 morbidly obese subjects during Roux-en-Y surgery. Insulin resistance biomarkers were measured using standard kits. Visfatin/Nampt, vaspin, and RBP-4 gene expression levels in tissues were measured using real-time PCR. Their protein concentrations in blood and tissues were measured using ELISA kits. Diabetic subjects had significantly higher homeostasis model of assessment-insulin resistance and age and lower blood HDL-cholesterol concentrations than nondiabetic and prediabetic subjects. Diabetic and prediabetic subjects had significantly higher blood concentrations of visfatin/Nampt and vaspin than nondiabetic subjects. Liver RBP-4 concentrations were positively associated with blood glucose concentrations. Blood insulin resistance biomarker levels were positively associated with visfatin/Nampt concentrations in omental adipose tissue and liver, and vaspin concentrations in mesenteric adipose tissue. In conclusion, the correlations of visfatin/Nampt, vaspin, and RBP-4 with insulin resistance are tissue dependent.